Small Neotropical primates promote the natural regeneration of anthropogenically disturbed areas - Heymann, Eckhard W.; Culot, Laurence [UNESP]; Knogge, Christoph; Smith, Andrew C.; Tirado Herrera, Emérita R.; Müller, Britta; Stojan-Dolar, Mojca; Lledo Ferrer, Yvan; Kubisch, Petra; Kupsch, Denis; Slana, Darja; Koopmann, Mareike Lena; et al. (Springer Nature, 2019)
Increasingly large proportions of tropical forests are anthropogenically disturbed. Where natural regeneration is possible at all, it requires the input of plant seeds through seed dispersal from the forest matrix. Zoochorous seed dispersal – the major seed dispersal mode for woody plants in tropical forests – is particularly important for natural regeneration. In this study, covering a period of more than 20 years, we show that small New World primates, the tamarins Saguinus mystax and Leontocebus nigrifrons, increase their use of an anthropogenically disturbed area over time and disperse seeds from primary forest tree species into this area. Through monitoring the fate of seeds and through parentage analyses of seedlings of the legume Parkia panurensis from the disturbed area and candidate parents from the primary forest matrix, we show that tamarin seed dispersal is effective and contributes to the natural regeneration of the disturbed area.